Effectiveness of Use of Ecdis on Navigation Safety: A Qualitative Study in Kl. Sultan Hasanuddin - Masrupah, Masrupah; Lestari, Endang; Yusuf, Dzakiyah Ulya; Farman, Indra; Pakadang, Grace Liku; Pratama, Andika Putra (PT. Hafasy Dwi Nawasena, 2024)
Maritime is a dynamic, ever-evolving world that demands innovative technology to improve shipping safety. The maritime world is facing significant changes rapidly, especially in the development and implementation of navigation technology. ECDIS or “Electronic Chart Display and Information System” is a tool whose function and system can provide information about navigation. The type of research carried out is descriptive qualitative research. This method is used to find knowledge about the research object. The type of research used is field research (field research), that is, researchers go directly into the field to search for and collect data. research location in KL. Sultan Hasanuddin. Determining the subjects of this research was purposive, and the data source chosen was the crew of the Kl ship. Sultan Hasanuddin PIP Makassar. The research results significantly increase shipping safety because digital maps have been prepared and reduced the workload of ship crews in making shipping routes. It is recommended that ships routinely update software and digital maps to ensure system accuracy and function, as well as provide training to ship crews every time there is a feature update on ECDIS